2019
DOI: 10.3390/ani9121088
|View full text |Cite
|
Sign up to set email alerts
|

Chewing and Drinking Activity during Transition Period and Lactation in Dairy Cows Fed Partial Mixed Rations

Abstract: Dairy cows need sufficient physically effective fibre (peNDF) in their diet to induce chewing with the latter stimulating salivation and maintaining rumen health. Thus, monitoring of chewing activity can be a non-invasive tool to assess fibre adequacy, and thus helping in the optimization of the diet. The objective of this study was to investigate and compare chewing activities of cows during transition period and in the course of lactation. Simmental dairy cows, in four different production groups such as dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…The third major activity was dedicated to feeding the assigned diet. In this study, the time eating the TMR was lower than the observed in dairy cows (30-38 kg of milk yield) in other studies ranging from 3.5 to 7.7 h/day [16][17][18]. However, the dietary supply on dairy cows was also much higher (approximately twice) than in this study.…”
Section: Discussioncontrasting
confidence: 77%
“…The third major activity was dedicated to feeding the assigned diet. In this study, the time eating the TMR was lower than the observed in dairy cows (30-38 kg of milk yield) in other studies ranging from 3.5 to 7.7 h/day [16][17][18]. However, the dietary supply on dairy cows was also much higher (approximately twice) than in this study.…”
Section: Discussioncontrasting
confidence: 77%
“…Indeed, as reported in our previous studies, the combined use of the two devices provides meaningful and accurate information regarding walking, feeding and rumination behaviors in dairy ruminants [18][19][20]. Sick and healthy cows seem to express different levels of activity [21], including parameters such as number of lying bouts [22], time spent lying down [23], length of strides [24], walking speed [24], chewing activity [25] feeding and rumination time [26,27]. Despite the amount of data available continues to increase, clinical consideration that may arise from them and consequently the systems for the early disease detection still show wide margins for improvement [9].…”
Section: Introductionmentioning
confidence: 61%
“…Cows in early lactation require high energy, which goes along with low feed intakes ( Brandstetter et al, 2019 ). Energy density, therefore, has to be increased in the diet leading to an enhanced SCFA production in the rumen ( Laffel, 1999 ; Saleem et al, 2012 ) and a decrease in rumen pH ( via increase of SCFA and lactate; Yang and Beauchemin, 2006 ; Derakhshani et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%